Addition of Illuminator Fiber Optic to Produce 3 Dimension Effects in Micrographic Observation Using Upright Microscope - Sutriyono; Widodo; Suryandari, Retno (Proceeding International Conference on Science and Engineering, 2020)
Microscope is one of the tools used in practicums with high intensity. The use of a microscope adjusts to the object to be observed in order to obtain optimal micrographic results. Stereo microscopes are used to observe three-dimensional objects. Upright microscopes are used to observe two-dimensional objects. This study aims to combine the two advantages of stereo microscopy that can produce three-dimensional micrography with the advantages of an upright microscope that has a high total magnification. The method used in this study is an experimental method by adding an optical fiber illuminator in the use of an upright microscope and then applying it in various observations. The conclusion of this research is the addition of an optical fiber illuminator in observations using an upright microscope can replace the function of a stereo microscope; can produce three-dimensional effects and increase magnification in Daphnia magna micrographic observations.